Potret Budaya Lokal Masyarakat Tanjung Raya, Kabupaten Agam - Sumatera Barat di Era Digital - Dwi Rini Sovia Firdaus; Djuara Lubis; Endriatmo Soetarto; Djoko Susanto (Jurnal Komunikasi Pembangunan, 2018)
The people of West Sumatra, who have been adhering to the Minangkabau matrilineal cultural tradition, are currently experiencing cultural decay. Many studies speculate that the unique Minangkabau culture will not be too much disturbed by the influx of globalization because in essence the only part that will be eroded is the peripheral part, while the core will remain preserved for all time. This study photographed the people of Tanjung Raya District based on existing family typologies, then saw a shift in norms passed on to teenagers using the six Hofstede cultural dimensions. This study surveyed five types of families with calculations using a simple addition operation. The results of the questionnaire were made high and low criteria, then presented in cobweb graphical form. The assessment indicators are based on the six dimensions of Hofstede's culture. Shifting the teachings of exemplary teachings from Minangkabau culture is determined using the ANOVA test. The results of this study are to map the portrait of Minangkabau culture according to Hofstede and a portrait of each of Hofstede's dimensions in each type of family in Tanjung Raya District. From there, it can be seen how far away the approach of the values taught by the family towards Minangkabau culture is approaching.